1989
DOI: 10.1161/01.hyp.13.5_suppl.i80
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum creatinine and effect of treatment of hypertension on renal function. Results from the hypertension detection and follow-up program. The Hypertension Detection and Follow-up Program Cooperative Group.

Abstract: on behalf of the Hypertension Detection and Follow-up Program Cooperative GroupThe Hypertension Detection and Follow-up Program followed up 10,940 persons for 5 years in a community-based, randomized, controlled trial of treatment for hypertension. Participants were randomized to one of two treatment groups, stepped care and referred care. The primary end point of the study was all-cause mortality, with morbid events involving the heart, brain, and kidney as secondary end points. Loss of renal function, ascert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
270
1
16

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 583 publications
(300 citation statements)
references
References 33 publications
11
270
1
16
Order By: Relevance
“…At the commencement of the study, 21 of 74 patients in group A and 25 of 78 in group B demonstrated echocardiographic evidence of LVH. When patients were divided into groups with or without LVH at the commencement of the trial (irrespective of treatment group), those with preexisting LVH demonstrated a significant decrease in LVMi (from 127 Ϯ 18 to 122 Ϯ 26 g/m 2 , n ϭ 33, P Ͻ 0.001) in 2 yr. Those with normal initial LVMi values exhibited an increase in LVMi (from 93 Ϯ 16 to 99 Ϯ 21 g/m 2 , n ϭ 84, P Ͻ 0.001); however, the changes were not related to [Hb]. The difference in the changes in LVMi in 2 yr between patients with and without LVH in baseline assessments was also significant (Ϫ3.9 Ϯ 19 versus 7.0 Ϯ 19 g/m 2 , P ϭ 0.006).…”
Section: Echocardiographic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the commencement of the study, 21 of 74 patients in group A and 25 of 78 in group B demonstrated echocardiographic evidence of LVH. When patients were divided into groups with or without LVH at the commencement of the trial (irrespective of treatment group), those with preexisting LVH demonstrated a significant decrease in LVMi (from 127 Ϯ 18 to 122 Ϯ 26 g/m 2 , n ϭ 33, P Ͻ 0.001) in 2 yr. Those with normal initial LVMi values exhibited an increase in LVMi (from 93 Ϯ 16 to 99 Ϯ 21 g/m 2 , n ϭ 84, P Ͻ 0.001); however, the changes were not related to [Hb]. The difference in the changes in LVMi in 2 yr between patients with and without LVH in baseline assessments was also significant (Ϫ3.9 Ϯ 19 versus 7.0 Ϯ 19 g/m 2 , P ϭ 0.006).…”
Section: Echocardiographic Resultsmentioning
confidence: 99%
“…Many studies examining mortality and morbidity rates among patients with CKD have identified high rates of cardiovascular events. When even mild renal insufficiency is associated with other risk factors for cardiovascular disease, the risk of subsequent cardiovascular events is significantly increased (2)(3)(4)(5)(6)(7)(8)(9)(10). The effect of mild renal insufficiency (serum creatinine levels of Ͼ124 M) on cardiovascular risk is possibly also independent of other known risk factors and treatment (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…In the Hypertension Detection and Follow-up Program trial, a linear relation between serum creatinine and cardiovascular mortality was observed over a 5-year follow-up, with a 2 times higher risk of mortality in patients with serum creatinine 41.7 mg/dl at baseline. 16 More recently, in the HOT study a slight increase in serum creatinine was associated with a 3.2 times greater incidence of fatal events, regardless of common cardiovascular risk factors. 7 Similar findings have also been reported by using creatinine clearance as an estimate of the glomerular filtration rate in patients with isolated systolic hypertension, 17 and in those with concomitant cardiovascular risk factors participating in the HOPE Study.…”
Section: Discussionmentioning
confidence: 97%
“…O tratamento da hipertensão arterial é uma das poucas medidas sabidamente efetivas em prolongar a sobrevida renal dos portadores de nefropatia das mais variadas etiologias 11,13 . Quanto maior o grau de proteinúria, mais intensamente a pressão arterial deve ser reduzida 9,10 .…”
Section: Introductionunclassified